Guía de los usos sociales, Rituales y Actos Festivos del Barrio Luz de América en honor a la Virgen del Quinche. - Lozano Veloz, Tamara Marianela (2020)
The present investigation is based on social uses, rituals and festive events from Luz de América. neighborhood of Poalo parish; in order to diagnose and inventory strengthen growth, cultural, economic and tourism, through the development of a descriptive guide. In the research process, three specific objectives were developed, which were carried out through descriptive-qualitative methodology application, which allowed to collect primary and secondary information to determine situational diagnosis of the area through the analysis of socio-economic and productive, cultural, and tourist factors where it was evidenced that the most of families that reside in the place, work in agriculture; This being the main income source as well as that few people have knowledge of the history and origin of the customs and festive traditions that are practiced year after year. For the pertinent registry and inventory, the methodology of National Institute of Cultural Heritage (INPC) was used, where a total of 5 festivals were recorded, among which the following Sub-scope religious festivals or ceremonies, festivals or commemorations and other festive celebrations are registered; Within this scope of festivities, it can be emphasized that in the organization and preparations to carry out these festivities, those are in charge of the neighborhood directive; accompanied by the prioste and volunteers who finance part of the activities; It is also customary to offer food such as baked with potatoes, soup or salad, chicha de jora and chicken broth, in the other hand, 1 ritual was registered with Sub-scope that is commemorative; In this it is characterized because the people who organize are independent; 4 practices were also registered with Subscope of Traditional Community Practices; It is important to mention that all the aforementioned have a low level of sensitivity to change. Finally, the design and printing of the guide is presented as a tool for cultural information; in turn, it generates benefits for residents and tourists. Through the dissemination of this study, a positive socio-economic impact is generated, which contributes to the conservation of knowledge about various Sub-Scope found, their traditions and gastronomic culture, increase tourist development of Luz de América neighborhood